A general framework for cultivating innovations in higher education curriculum. Issue 3 (16th April 2019) - Bajada, Christopher; Kandlbinder, Peter; Trayler, Rowan
ABSTRACT: Systematic changes to higher education curriculum typically occur within the extended timeframes of formal curriculum review processes. Programmes need to be reviewed periodically for internal and external accountability or to determine whether the curriculum has lost its coherence due to the accumulative effect of continual small-scale changes. These programme reviews often lend themselves to the introduction of innovations in teaching and learning however experiences suggest that these innovations are often short-lived. Even with well-thought-through project plans, adequate funding and staffing, and robust project evaluations, a curriculum innovation may fail to take hold and continue beyond the short-term. In this article we work towards developing a general framework that identifies the various factors and drivers that are essential to sustain important curriculum innovation beyond the short-term. The framework is developed from an analysis of several curriculum innovations related to the embedding of graduate attributes to highlight the important factors necessary to ensure longevity in important developments in teaching and learning.